Autonomy or integration: Historical analysis of the debate on the purpose of Icelandic local self-government - Eva Marín Hlynsdóttir (Veftímaritið Stjórnmál og stjórnsýsla, 2018)
An ongoing debate on the purpose of local self-government in Iceland has been simmering mainly between those who believe that local authorities should amalgamate in order to assume more responsibilities and those who believe that local autonomy, understood as the right of citizens to govern their own jurisdictions, should not be weakened. The purpose of this study is to discuss the role of local self-government in Iceland from these two very different perspectives by situating it within the context of the Nordic model of local self-government. This study’s findings reveal that the Icelandic central government has successfully introduced functional reforms at the local level over the past 25 years, but it has not been as successful in initiating territorial reforms. The findings also show that conflict between the ideologies of the traditional autonomous model and the more modern model of integration is growing.